2018
DOI: 10.2135/cropsci2017.07.0450
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Parent Maize (FPM) Population: Development and Phenotypic Characterization

Abstract: To measure the effectiveness of multiparent population design in maize (Zea mays L.), an unprecedented, four‐parent maize (FPM) population was developed, incorporating a series of different mating designs. The FPM population incorporated up to three generations of intermating to allow for comparison of traditional biparental, multiparent, and multiparent intermated populations for phenotypic diversity. A total of 1291 inbred lines were evaluated per se with at least one replication among 5551 total progeny plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
(36 reference statements)
0
17
1
Order By: Relevance
“…Furthermore, individuals with high heterozygosity (> 20%) were removed resulting in 1149 individuals including: 126 B73Olc1 × Tx903, 112 Tx772 × Tx906, 107 4way0sib, 212 4way1sib, 93 4way2sib, and 491 4way3sib; eight were 4way (based on the observed parental allele contribution frequencies) but their intermating level was misplaced. For detailed methods on genotyping the FPM population refer to Mahan (2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, individuals with high heterozygosity (> 20%) were removed resulting in 1149 individuals including: 126 B73Olc1 × Tx903, 112 Tx772 × Tx906, 107 4way0sib, 212 4way1sib, 93 4way2sib, and 491 4way3sib; eight were 4way (based on the observed parental allele contribution frequencies) but their intermating level was misplaced. For detailed methods on genotyping the FPM population refer to Mahan (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Meng et al (2016) demonstrated increased QTL identification power and faster LD decay distance in the 8‐way Indica rice MAGIC population compared to the 4‐way. Currently MAGIC populations (reviewed by Huang et al, 2015) have been developed in Arabidopsis (Kover et al, 2009), rice (Bandillo et al, 2013; Meng et al, 2016), wheat (Huang et al, 2012; Mackay et al, 2014), durum wheat (Milner et al, 2016), barley (Sannemann et al, 2015), dry bean (Lobaton et al, 2015), tomato (Pascual et al, 2015), sorghum (Higgins et al, 2014) and maize (Dell'Acqua et al, 2015; Mahan et al, 2018).…”
mentioning
confidence: 99%
“…Genetic variation of terminal plant height (PHT TRML ) in maize ( Zea mays L.) is a highly heritable trait (Anderson et al, 2018; Li et al, 2016b; Mahan et al, 2018; Peiffer et al, 2014; Wallace et al, 2016) and is relatively easy to phenotype, for instance measuring from the ground to the tip of a tassel on a representative plant. However, the labor and time required to collect data is still resource constrained, and height measurements collected in maize research programs are generally taken only once, when the plants have reached maximum growth after the completion of flowering.…”
mentioning
confidence: 99%
“…Quantitative variation of complex traits in maize ( Zea mays L.) have been challenging to dissect since they show strong environmental interactions and are generally inconsistent between populations and different screening environments (Beavis et al., 1991; Koester et al., 1993; Peiffer et al., 2014; Sari‐Gorla et al., 1999; Veldboom & Lee, 1996; Wang et al., 2006). Plant height, traditionally measured terminally at the end of the growing season with a ruler, is a prime example of a quantitative, complex trait; it is relatively easy to measure across many plots and it has high repeatability and heritability (Anderson et al., 2018,2019, 2020; Mahan et al., 2018; Peiffer et al., 2014; Rood & Major, 1981; Veldboom & Lee, 1996). Genetic mapping and theory suggest an omnigenic model supported by the genetically polygenic inheritances observed and the variable contributions of pedigree as a source of variation, consistent with a large number of loci with minor effects governing these traits (Boyle et al., 2017; Mackay, 2001; Peiffer et al., 2014; Wallace et al., 2016; Wang et al., 2006).…”
Section: Introductionmentioning
confidence: 99%